Evaluation of a Bidentate ‘Clamp-Like’ Halogen-Bond Donor Motif Based on Iodonium(III) Moieties - Reinhard, Dominik L.; Kutzinski, Dana; Hatta, Masahito; Engelage, Elric; Huber, Stefan M. (Synlett, 2023)
A new motif for iodine(III)-based halogen-bond donors consisting of a 1,3-phenylene core and two cyclic five-membered diaryliodonium(III) wings was designed and its potential as a catalyst was evaluated. Its properties were analyzed in the solid state by X-ray crystallography and in solution by benchmark catalytic activation of a nitro-Michael addition between 5-methoxyindole and trans-β-nitrostyrene.
Keywords: halogen bonding; hypervalent iodine; structure–activity relationship; organocatalysis; diaryliodonium